Facile and Reliable Emission‐Based Nanomolar Anion Sensing by Luminescent Iridium Receptors Featuring Chelating Halogen‐Bonding Sites - Kampes, Robin (Chemistry, 2020)
An anion sensor is presented that combines a bidentate hydrogen‐ (HB) or halogen‐bonding (XB) site with a luminescent monocationic Ir fragment for strong binding of common anions (K (a) up to 6×10(4)  m (−1)) with diagnostic emission changes. A new emission‐based protocol for fast and reliable detection was derived on the basis of correction for systematic but unspecific background effects. Such a simple correction routine circumvents the hitherto practical limitations of systematic emission‐based analysis of anion binding with validated open‐source software (BindFit). The anticipated order of K (a) values was obeyed according to size and basicity of the anions (Cl>Br=OAc) as well as the donor atom of the receptor (XB: 6×10(4)  m (−1) > HB: 5×10(3)  m (−1)), and led to submicromolar limits of detection within minutes. The results were further validated by advanced NMR techniques, and corroborated by X‐ray crystallographic data and DFT analysis, which reproduced the structural and electronic features in excellent agreement. The results suggest that corrected emission‐based sensing may become a complementary, reliable, and fast tool to promote the use of XB in various application fields, due to the simple and fast optical determination at high dilution.